2013
DOI: 10.1007/s10714-013-1652-4
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of quantum channel of radiation in pure Lovelock black holes

Abstract: It is known that the emission rate of entropy from a Schwarzschild black hole is exactly the same as that of a one dimensional quantum channel [1]. We calculate the dimension of entropy emission from a D dimensional pure Lovelock black holes. Our results indicate that the dimension of transmission for odd D dimensional space-times is equal to D and for even D dimensional spacetimes, the dimension of quantum channel becomes 1 + ǫ(Λ), where Λ is cosmological constant. It is interesting that cosmological constant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The strong inequality (12) implies, in particular, that, in the large-D limit, the black-hole emitted quanta are practically unaffected by the curvature potential. Thus, one concludes that, in the large D 1 limit, the evaporating black holes behave as D-dimensional perfect black-body emitters (formally, this last conclusion is exact in the D → ∞ limit), in which case the emission power is given by the geometric-optics (short wavelengths) approximation [10]:…”
Section: Quantum Evaporation Of Higher-dimensional Schwarzschild Blacmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong inequality (12) implies, in particular, that, in the large-D limit, the black-hole emitted quanta are practically unaffected by the curvature potential. Thus, one concludes that, in the large D 1 limit, the evaporating black holes behave as D-dimensional perfect black-body emitters (formally, this last conclusion is exact in the D → ∞ limit), in which case the emission power is given by the geometric-optics (short wavelengths) approximation [10]:…”
Section: Quantum Evaporation Of Higher-dimensional Schwarzschild Blacmentioning
confidence: 99%
“…After this paper was completed, I have been informed that Mirza, Oboudiat, and Zare [12] have also studied the entropy emission rate of higher-dimensional black holes. It is worth emphasizing that the analysis presented in [12] incorrectly assumes that the radiating area of a D-dimensional Schwarzschild black hole is given by its surface area A H = [2π D/2 / (D/2)]r D−1 H .…”
Section: Note Addedmentioning
confidence: 99%
See 1 more Smart Citation
“…We introduce particle model to a rather interesting area of modified theory of gravity which is called pure Lovelock gravity (pLG). This terminology was used for the first time by Kastor and Mann [1] and has been developed by Cai, et al [2,3], Dadhich, et al [4][5][6][7][8][9][10][11][12][13] and others [14][15][16][17][18]. We recall from the original Lovelock theory that the action of the n + 1−dimensional n 2 -order Lovelock gravity is given by [19]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the analysis is completely new, which once again tells that gravitational anomalies have a leading role to play in the thermodynamics of black holes. Let me finish mentioning existing work [35] which discussed a similar topic for the arbitrary D space dimensional Schwarzschild black hole and the black hole in Lovelock gravity. It was found that the dependence ofṠ on P is not like the Pendry for Lovelock case, which, as pointed out in [3], is due to an improper choice of the radiating area.…”
mentioning
confidence: 99%